(untitled) (Acta Scientiarum. Health Sciences, 2017)
A non-linear mixed-effects model is proposed to assess the impact of acarbose over time on postprandial glycaemia in a single rat. The model is based on two compartments, one representing the entry of glucose in the blood and the other its exit. The rat was submitted to two treatments: ingestion of starch and ingestion of starch plus acarbose. The model showed great suitability, with inferences on the behavior of glucose levels in response to treatments and supplying a richer description than just the area under the curve. The marginal curves for the two treatments are similar during the first moments; however, after reaching the peak of glucose concentration, they progressively became separate due to acarbose treatment and reached the initial levels more quickly. The proposed model, albeit with a single sample unit, showed similar results to those with larger samples; in other words, acarbose significantly attenuates glycaemia after ingestion of starch.